Masalah yang Dialami Perawat Dalam Menangani Remaja Penyalahguna NAPZA: A Systematic Review - Dwi Suratmini; Novy Helena Catharina Daulima (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Nurse’s efforts in adolescent as the most drug-abusing population have not been able to run optimally as indicated by the increase in prevalence and relapse rates, so further studies are needed regarding the problems experienced by nurses during the handling process. The aim of this systematic review was to find out the problems experienced by nurses while dealing in adolescent drug users. The database were used EBSCOhost, ProQuest, Sage Publication, and Springerlink identified and published from 2016-2020, in English, and in the nurse population both in hospitals or other rehabilitation. The keywords were "adolescent * OR youth * OR teen *" AND "nursing intervention" OR "nursing care" AND "drug abuse" OR "drug misuse" OR "drug addiction. Article identification was carried out using the PRISMA guidelines. Based on the inclusion and exclusion criteria there were 9 relevant articles. Analysis illustrated the existence of internal and external problems experienced by nurses. Internal problems consisted of values, morals, and perceptions. External problems consisted of the characteristics of youth development tasks, agency policies, and socio-cultural conditions. These problems affected the interaction of nurses with clients, family, peers, and other professions. Increased knowledge and ability of nurses as well as a review of policies in providing nursing care can be done to overcome internal and external problems experienced by nurses to optimize their duties and roles in dealing with adolescent drug users. Keywords: problems; nursing care; adolescent drug abusers ABSTRAK Upaya perawat dalam mengatasi masalah remaja sebagai populasi terbanyak penyalahguna NAPZA hingga saat ini belum dapat berjalan optimal ditunjukkan dengan meningkatnya angka prevalensi dan kekambuhan, sehingga diperlukan kajian lebih lanjut mengenai masalah yang dialami perawat selama proses penanganan. Systematic review ini dilakukan untuk mengetahui masalah yang dialami perawat selama menangani remaja penyalahguna NAPZA. Penelusuran literatur secara sistematis melalui database EBSCOhost, ProQuest, Sage Publication, dan Springerlink. Artikel yang digunakan berada pada tahun 2016-2020 dan berbahasa Inggris pada populasi perawat baik di rumah sakit atau lembaga rehabilitasi lainnya. Kata kunci yang digunakan adalah “adolescent* OR youth* OR teen*” AND "nursing intervention" OR "nursing care" AND "drug abuse" OR "drug misuse" OR "drug addiction”. Identifikasi artikel dilakukan menggunakan pedoman PRISMA. Berdasarkan kriteria inklusi dan eksklusi terdapat 9 artikel relevan. Analisa artikel menggambarkan adanya masalah internal dan eksternal yang dialami perawat dalam menangani remaja penyalahguna NAPZA. Masalah internal terdiri dari nilai, moral, dan persepsi. Masalah eksternal terdiri dari karakteristik tugas perkembangan remaja, kebijakan instansi, dan kondisi sosial budaya. Masalah tersebut mempengaruhi interaksi perawat dengan klien, keluarga, rekan sejawat, dan profesi lain. Peningkatan pengetahuan dan kemampuan perawat serta peninjauan kembali kebijakan dalam pemberian asuhan keperawatan dapat dilakukan untuk mengatasi masalah internal dan eksternal yang dialami perawat untuk mengoptimalkan tugas dan perannya dalam menangani remaja penyalahguna NAPZA. Kata kunci: masalah; penanganan perawat; remaja penyalahguna napza